The "GOOD GUY WITH A GUN” CONCEPT IN THE AMERICAN GUN CULTURE AND GUN CONTROL POLICY - Mazur, Karol (Scientific Journal of Bielsko-Biala School of Finance and Law, 2021)
The United States has one of the most controversial gun laws in the modern world. The characteristic feature of this country is a gun culture legitimate in constitutional law. An important aspect of gun culture is a set of concepts used by gun rights activists. One of them is the term described in the American discourse as the “good guy with a gun”. The article contains information on this concept and its interpretation as well as presentation of its forming elements. Also, it attempts to offer an understanding of the phenomenon of its popularity in the public debate. Keywords: good guy with a gun, right to keep and bear arms, gun culture, Second Amendment.